Local Overheating of Biotissue Labeled With Upconversion Nanoparticles Under Yb3+ Resonance Excitation - Krylov, Ivan V.; Akasov, Roman A.; Rocheva, Vasilina V.; Sholina, Natalya V.; Khochenkov, Dmitry A.; Nechaev, Andrey V.; Melnikova, Nataliya V.; Dmitriev, Alexey A.; Ivanov, Andrey V.; Generalova, Alla N.; Khaydukov, Evgeny V. (Frontiers in Chemistry, 2020)
Local overheating of biotissue is a critical step for biomedical applications, such as photothermal therapy, enhancement of vascular permeability, remote control of drug release, etc. Overheating of biological tissue when exposed to light is usually realized by utilizing the materials with a high absorption cross section (gold, silica, carbon nanoparticles, etc). Here, we demonstrate core/shell NaYF4: Yb3+,Tm3+/NaYF4 upconversion nanoparticles (UCNPs) commonlyly used for bioimaging as a promising near-infrared (NIR) absorbers for local overheating of biotissue. We assume that achievable temperature of tissue labeled with nanoparticles is high enough due to Yb3+ resonance absorption of NIR radiation while the use of auxiliary light-absorbing materials or shells is optional for photothermal therapy. For this purpose, a computational model of tissue heating based on the energy balance equations was developed and verified with the experimentally obtained thermal-graphic maps of a mouse in response to the 975-nm laser irradiation. Labeling of biotissue with UCNPs was found to increase the local temperature up to 2°C compared to that of the non-labeled area under the laser intensity lower than 1 W/cm2. The cellular response to the UCNP-initiated hyperthermia at sub-critical ablation temperatures (lower than 42°C) was demonstrated by measuring the heat-shock proteins overexpression. This indicates that the absorption cross section of Yb3+ in UCNPs is relatively large, and microscopic temperature of nanoparticles exceeds the integral tissue temperature. In summary, a new approach based on the use of UCNP without any additional NIR absorbers was used to demonstrate a simple approach in the development of photoluminescent probes for simultaneous bioimaging and local hyperthermia.